Acceptance of Disability and Hwa-Byung among Korean Mothers of Children with Developmental Disabilities - Kim, Eunha; Hwang, Jowon; Park, Sukyoung (International Journal of Disability, Development and Education, 2018)
This study examined how child problem behaviour could be related to maternal Hwa-Byung (HB; Korean culture syndrome, meaning ‘anger illness’) among Korean mothers of children with developmental disabilities. Acceptance of disabilities and parenting stress were tested as mediators for the relationship between child problem behaviour and maternal HB. The results indicated that child problem behaviour alone (e.g. self-injurious and aggressive behaviours, yelling/screaming, and crying) were not related to maternal HB. Instead, child problem behaviour was not directly associated with maternal HB, but indirectly related to maternal HB through decreased acceptance of disability and increased parenting stress. The findings of the study support the importance of Acceptance and Commitment therapy and parenting stress intervention to prevent and treat HB among Korean mothers of children with developmental disabilities.
Keywords: Acceptance of disabilities; children; developmental disabilities; Hwa-Byung; Korean; mothers; parent education; parenting stress